The effectiveness of coconut-dreg-based mudballs in kitchen wastewater treatment from restaurants and poultry shops - Maklen, Nur Sabrina; Shafie, Farah Ayuni; Abdullah, Norhidayah; Abdul Aziz, Saidatul Afzan; Ishak, Noriza (Faculty of Health Sciences, Universiti Teknologi MARA, 2025)
This study investigates the effectiveness of coconut-dreg-based mudballs as a sustainable and cos effective solution for treating kitchen wastewater from restaurant and poultry shop sources. Kitchenwastewater, characterized by its high organic load and potential pathogen content, poses significaenvironmental and public health risks if not adequately treated. Leveraging the principles of circuleconomy and sustainable waste management, coconut dregs, a by-product of the food industry, aharnessed for their potential in bioaugmentation to develop mudballs for wastewater treatmenMudballs is a well-known biological treatment method for wastewater. Laboratory experimentwere conducted to assess the removal efficiency of pollutants, including pH, dissolved oxygen (DOturbidity, chemical oxygen demand (COD), and ammoniacal nitrogen, comparing the performancof coconut-dreg-based mudballs with conventional mudballs. Coconut- dreg-based mudbaldemonstrated significant turbidity reduction (91.33%), COD reduction (84.84%), and effectivammoniacal nitrogen reduction (89.13%), particularly in kitchen wastewater from restaurants. Thalkaline and fibrous nature of coconut dregs were identified as the key factors contributing to thesfavourable results. The enhanced effectiveness of coconut-dreg-based mudballs highlights theviability as a cost-effective and environmentally friendly alternative for kitchen wastewattreatment.